Effectiveness Test of the PRISMA-E’xi Learning Model in Physics Learning: A Large-Scale Trial on Creative Problem Solving Across Rural, Sub-Urban, and Urban Schools - Rahma Diani; Viyanti Viyanti; Tri Jalmo; Dewi Lengkana; Hendri Noperi; Antomi Saregar; Fredi Ganda Putra (FOUNDAE (Foundation of Advanced Education), 2026)
This study investigates the effectiveness of the PRISMA-E’xi learning model—an instructional innovation that integrates a multi-representation approach with the Engineering Design Process (EDP) in a STEM framework—to enhance senior high school students’ creative problem-solving (CPS) skills in physics. Employing a quantitative quasi-experimental design with a nonequivalent control group, the research involved 350 students from five schools representing rural, suburban, and urban regions. Students in the experimental group (n = 175) received instruction using PRISMA-E’xi, while those in the control group (n = 175) experienced conventional teaching. CPS ability was assessed through pre- and posttests aligned with six indicators: objective finding, fact finding, problem finding, idea finding, solution finding, and acceptance finding. Data were analyzed using independent t-tests, effect size (Cohen’s d), one-way ANOVA, and MANOVA with prerequisite tests for normality and homogeneity. Results revealed a highly significant improvement in CPS for the experimental group (t(342) = 17.8, p < 0.001) with a large effect size (d = 1.92). One-way ANOVA indicated no significant differences in n-gain across regions (p = 0.707), and MANOVA confirmed a strong multivariate effect of the learning model (Pillai’s Trace = 0.5027, p < 0.001) on all CPS indicators without regional interaction effects. Each instructional syntax of PRISMA-E’xi—problem exploration, representation structuring, investigative reasoning, scientific modelling, model assessment, and adaptive reflection—was found to foster specific CPS indicators, supporting critical and creative thinking as well as adaptive reasoning. Guided reflection, multi-representation analysis, and iterative solution evaluation promoted deep conceptual understanding and transferable problem-solving skills. The findings demonstrate that PRISMA-E’xi is an effective, flexible, and equitable model for improving students’ creative problem solving in physics, independent of geographic context. Despite limitations related to the quasi-experimental design, limited duration, and sample scope, the study provides robust empirical evidence that PRISMA-E’xi can serve as a scalable and innovative framework for 21st-century competency-based science education. Future research should employ randomized or longitudinal designs and explore cross-disciplinary applications to strengthen external validity and long-term impact assessment.